Intervention of Self-Advocacy Skill Among Individual with Special Needs: A Systematic Literature Reviewof Self-Advocacy Skill Among Individual with Special Needs: A Systematic Literature Review - Nuri , Norzaliana Mat; Ali , Manisah Mohd; Salleh, Norshidah Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
— Self-advocacy is essential skills for the individual with special needs. Since 30 years ago, researchers had used various initiatives to develop and improve self-advocacy skills among individuals with specials needs. Various initiatives have been taken by researchers including creating self-advocacy movement, introducing self-advocacy in internationals seminars, and designing transition programs for disabled relating to the importance of self-advocacy. According to these previous studies, a systematic literature review has been conducted to study on intervention of self- advocacy skills among the individuals with special needs. Articles were searched from years 2013 to 2018 by using Scopus and EBSCOhost as the main journal databases. There are three main objectives on this study, firstly is to identify literature review on interventions that had been conducted during the prescribed period, secondly to evaluate the effectiveness of interventions on individuals with specials needs and lastly to determine the patterns of intervention that apply to individuals with specials needs. The research design approaches were qualitative and quantitative (quasi- experimental, single subject experimental and group experiments) are included for this systematic analysis. The limitation of this study is only literatures on intervention of self-advocacy skill studies are selected to review. The importance of this study is to provide information on interventions of self-advocacy skills that have been conducted and to evaluate the effectiveness of such interventions on individuals with specials needs. This study can also be used as a guide in planning an intervention programme for individuals with special needs especially for schools, specific agencies and government bodies.